Innovation and sectoral employment: A trade-off between compensation mechanisms - Bernd Ebersberger; Andreas Pyka (Universität Augsburg, Institut für Volkswirtschaftslehre, 1999)
The question whether technological progress displaces employment or whether technological advance is beneficial for the level of employment has been in the core of economic dispute for over two centuries. The beneficial might be achieved by several compensation mechanisms within the economic system. In this paper we categorize these compensation mechanisms into two basic categories that reflect the different nature of the ideas ruling the compensation. We discriminate the mechanisms employment despite of innovation from employment via innovation. In the context of new innovation economics we model an artificial industry implementing both compensation mechanisms. Simulation analysis is used to examine the short run and the long run properties of the model. There we focus on the influence of wage restraint policy on the functioning of the compensation mechanism.
urn:nbn:de:bvb:384-opus4-276770
Keywords: J3; L2; O3; 330; Innovation; employment; compensation-mechanisms; simulation; evolutionary economics